Surgical Revascularization of Chronically Occluded Coronary Arteries—What You See Is What You Get? - Gestrich, Christopher; Lagemann, Doreen; Duerr, Georg Daniel; Konrad, Nicole; Sinning, Jan-Malte; Mellert, Fritz (The Thoracic and Cardiovascular Surgeon, 2019)
Background Revascularization strategy in coronary artery bypass grafting (CABG) surgery usually depends on coronary dimension and stenosis severity. Little is known about the relation of preoperative evaluation of scarcely or invisibly chronic occluded coronary arteries (chronic total occlusion [CTO]) and revascularization rate or anastomosis quality. We aimed to evaluate the success rates of CTO revascularization in CABG surgery and determine the influence of coronary lumen visibility and collateralization in preoperative angiograms on revascularization rates, bypass blood flow, and target vessel diameter.Method Preoperative coronary angiograms were evaluated for 938 consecutive patients who underwent isolated CABG surgery between 2014 and 2016 and screened for occluded coronary arteries. The occluded vessels were scored for visibility using the Rentrop grading of collateral filling. Intraoperatively, dimensions of the occluded arteries were measured using conventional vessel probes, and anastomosis quality was assessed by transit time flow measurement.Results A total of 404 (43.1%) patients were identified with at least one CTO. Revascularization rates differed from 96.2% in the left anterior descending artery, to 85.0% in left circumflex artery-dependent vessels, and 78.8% in right coronary artery territory. Coronary visibility and grade of collateralization in the preoperative angiogram had no influence on intraoperatively measured coronary diameter. Bypass blood flow in grafts revascularizing CTOs lacking collateralization were not significantly lower than those grafts leading to CTOs with higher Rentrop scores.Conclusion Preoperative coronary assessment often differs from intraoperative findings. Our study confirms that even patients with scarcely collateralized CTOs and impaired visibility in the coronary angiogram have a high chance of complete revascularization during CABG surgery.
Keywords: chronic total occlusion; CTO; complete revascularization; CABG; surgical revascularization